2016
DOI: 10.1007/jhep11(2016)011
|View full text |Cite
|
Sign up to set email alerts
|

Measuring c-quark polarization in W +c samples at ATLAS and CMS

Abstract: Being able to measure the polarization of quarks produced in various processes at the LHC would be of fundamental significance. Measuring the polarizations of quarks produced in new physics processes, once discovered, can provide crucial information about the new physics Lagrangian. In a series of recent papers, we have investigated how quark polarization measurements can be done in practice. The polarizations of heavy quarks (b and c) are expected to be largely preserved in the lightest baryons they hadronize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 85 publications
(168 reference statements)
0
8
0
Order By: Relevance
“…Note that the depolarization parameters A and ω 1 are measurable at Atlas, BaBar, Belle, CMS and LHCb [64]. The Λ c polarization itself is measurable at Atlas, CMS and LHCb via pp → t(→ bW + (→ cs))t(→bW − (→ l −ν )) [64] and pp → W − c [65], where P (W − ) c −0.97 [68]. The angular asymmetry is shown in figure 6 for P Λc as expected at the Z, eq.…”
Section: On λ C → Pγmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the depolarization parameters A and ω 1 are measurable at Atlas, BaBar, Belle, CMS and LHCb [64]. The Λ c polarization itself is measurable at Atlas, CMS and LHCb via pp → t(→ bW + (→ cs))t(→bW − (→ l −ν )) [64] and pp → W − c [65], where P (W − ) c −0.97 [68]. The angular asymmetry is shown in figure 6 for P Λc as expected at the Z, eq.…”
Section: On λ C → Pγmentioning
confidence: 99%
“…Prerequisite for an interpretation of A γ is a measurement of the Λ c polarization, however, irrespective of its precise value, in the SM A γ is expected to be positive at the Z. The branching ratio of Λ c → pγ may be investigated at Belle II [2], the depolarization fraction at the LHC [65], and at the FCC-ee [19] all of this including A γ .…”
Section: On λ C → Pγmentioning
confidence: 99%
“…where the parametrization of [17,18,19] is used. The polarization is measurable at future colliders as well as BaBar, Belle and LHC.…”
Section: The Decay λ C → Pγmentioning
confidence: 99%
“…on e + e − annihilations, the decay of the Z boson to a heavy quark-antiquark pair also shows a significant degree of longitudinal polarization which amount to P b = −0.94 for bottom quarks and P c = −0.68 for charm quarks [16]. In a sequence of papers the possibility to measure the polarization of bottom (and charm) quarks at ATLAS and CMS has been analyzed [17,18,19,20]. The authors come to an affirmative answer, though the quarks are observed only as a jet of hadrons.…”
Section: Introductionmentioning
confidence: 99%